Analysis of entry into different mystery shopping markets within a global company - Čubová, Lenka; Hnilica, Jiří, 1976-; Sieber, Patrik, 1977-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2017)
This thesis deals with the topic of internal outsourcing of mystery shopping management within the multinational company Ipsos. The company has currently set up a Global Support Center for mystery shopping in Prague. The Global Support Center is supposed to create shopper panels (i.e. groups of mystery shoppers available to conduct mystery shopping tasks in a given country) in as many countries as possible and manage mystery shopping projects in these countries from the Czech Republic. The goal of this thesis is to find the most suitable market for the shopper panel construction, the market where panel construction is a priority over other markets.After analysing the different markets worthy of consideration through an application of the CAGE analysis and the Porter´s Five Forces, France has been chosen as the most reasonable market to pursue when constructing the shopper panels.
Vedoucí práce: Jiří Hnilica
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses